Maha Puja Navarathiri & Vijaya Dhasamiumat Hindu at the Sri Mariaman Temple in Medan City - Agung Suharyanto; Wiflihani; Onggal Sihite; Yesti Pratiwi; Ijon Gabe Martuah Sinaga; Yesima Sidebang; Andreas; Lamroito Lumbantoruan; Lia Finola Pasaribu; Rohaida Febriani Nasution; Lusianni Limbong; Sonia Wahyuni Daulay; Anjelia Tarigan; Sulistiah Rachmah (Lakhomi Journal Scientific Journal of Culture, 2020)
This research is a research conducted to determine the procedures, components of the ceremony, and to know the function and meaning of the Nava Rathiri and Vijaya Dhasami celebrations for Hindus in Medan City. This study used qualitative research methods and data collection was carried out by following the ceremony held directly by the Maha Puja Navarathiri & Vijaya Dhasamiumat Hindu ceremony at the Sri Mariaman Temple, Medan City. This research was conducted at the Srimariaman temple, where the navaratri is carried out for nine days every night in a row by Hindus living in the city of Medan. The result of this research is that this celebration is a worship for goddesses who have fought long ago against evil, namely giants. This celebration performed at Worship was done to please the goddesses for nine days as many days as it took for the goddess to defeat the evil monster. This is in accordance with its implementation, which is for nine days in the Tamil month of purification. There are many components used in this statement, from a series of flowers, coconut, trinkets, and many more. Worship is done to restore the good qualities of humans and defeat the bad qualities in humans because basically every human being is created for good. There are many components used in this statement, from a series of flowers, coconut, trinkets, and many more. Worship is done to restore the good qualities of humans and defeat the bad qualities in humans because basically every human being is created for good. There are many components used in this statement, from a series of flowers, coconut, trinkets, and many more. Worship is done to restore the good qualities of humans and defeat the bad qualities in humans because basically every human being is created for good.